DAMPAK EKPSANSI REGIONAL OPERATOR SELULER XL AXIATA MALAYSIA DI INDONESIA (2007-2013) - Elia Febrina Anggraini; Tri Joko Waluyo, (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2014)
This study used qualitative research methods that the urce datais taken from books, journals, newspapers, internet, and previousresearch has relevant data with the title.The perspective used in thisstudy is perspektif liberalism and the theory of investment. By usinggroup level behavior analysis, the main focus is to study the behavior ofgroups and organizations involved in international relations.This study will describe the impact of the expansion o Malaysianmobile operator XL Axiata in Indonesia against the gov ent and thetelecommunications sector economic development Indonesia. to knowhow the Indonesia government in making policy liberalization in theIndonesia telecommunications sector against foreign in estment,especially for XL Axiata majority of 66 percent stake owned by Malaysiagets ease contained in Article 5 of Presidential Regul tion No. 77 of2007, implementation of the legislation No. 25 Year 2007 on Investmentand to see the impact of expansion XL Axiata increasingly aggressivelyexpand and develop the business by way of acquisition f PT AxisTelecom Indonesia, raises concerns for telecommunications Indonesiaespecially against Telkomsel and Indosat.expansion, liberalization of telecommunications, legislation,acquisitions.